Проблемы и решения локальной вычислительной сети крупного предприятия - Слюсаренко, Ю. А.; Шипулин, А. А.; Гриневич, Ю. С.; Максимов, Р. В. (НТУ "ХПИ", 2014)
В статті наведено огляд основних сучасних мережевих технологій та показана еволюція комп’ютерної локальної обчислювальної мережі крупного підприємства на прикладі ДП ХКБМ імені О. О. Морозова – від найпростіших міні-мереж підрозділів до корпоративної ЛОМ, яка дозволяє впровадити на великому підприємстві CAE-CAD-CAM технології, а в майбутньому – Автоматизовану електронну систему управління підприємством.

In article there is a review of the basic modern network technologies and evolution local computer network of the large enterprise on an example of SE KMDB – from the elementary mini-networks of divisions to corpo-rate a LAN is shown, allowing to introduce at large enterprise CAE-CAD-CAM of technology, and in the long term – the Automated electronic control system of the enterprise.
Problems and decisions of the local computer network of the large enterprise
Keywords: сетевые технологии; компьютерные сети; локальные вычислительные сети; глобальная сеть; интернет; оборудование компьютерных сетей; способы коммуникации; сетевые устройства